Pediatric Extraskeletal Ewing Sarcoma Originating in the Heart: A Case Report and Review of the Literature. Issue 4 (29th May 2021) - Buffoni, Isabella; Nuri, Halkawt; Pome', Giuseppe; Sementa, Angela R.; Stagnaro, Nicola; Barra, Salvina; Manzitti, Carla; Garaventa, Alberto
Abstract : Extraosseous Ewing sarcoma of primary cardiac origin is an extremely rare variety among pediatric cardiac neoplasms. We report a case of extraosseous Ewing sarcoma of primary cardiac origin in a 9-year-old girl, treated with debulking surgery, adjuvant chemotherapy, and radiotherapy.